Reflexión: Las competencias desde la perspectiva educacional con una propuesta perfil del docente en establecimientos vulnerables (Educational Perspectives Magazine (REPED), 2022)
The issue of skills in recent years has gained enormous importance, for the increasing demand of highly competent and specialized professionals.The concept of competencies, thus understood, is an attempt to deepen the educational task of developing skills in individuáis to tackle the challenges of living, independent of the material conditions. However, this concept is limited if restricted to the development of individual capabilities, obviating the collective construction of meaning, the development of joint action or building bridges of trust within society. The concept of competencies is greatly reduced if is not altogether, in its formulation, of a profound reflection on the role of education in the current social orden.Currently, we do not have a profile for teachers who work in establishments of vulnerability that needs well-trained teachers with high expectations for student success and high self-esteem of these.Therefore, it presents a challenge for teachers, so they can tum around from his academic training, to one based on the needs of society, and move from a focus on education to one focused on leaming students.From questions asked to different social and educational, we can discem that has been given greater emphasis on specific skills related to the professional areas (disciplinary and teaching), rather than arcas of social and community projection of the profession. The challenge is to check the curriculum policies to meet the social and cultural diversity of Latin America, including special needs of groups and ethnic minorities.